(untitled) (AUN INTERNATIONAL CONFERENCE, 2024)
This research investigated the impact of corporate governance disclosure on stock price reaction of consumer goods firms listed on the Nigeria Stock Exchange (NSE). The study involved 16 consumer goods firms listed on the NSE. Secondary data for the study was collected from the annual reports of the sample companies, for the period 2014 to 2022. The panel data regression analysis, particularly the feasible generalized least square regression (FGLS) method was used because it has an inbuilt mechanism to control for the existence of heteroskedasticity and accommodate non-normally distribution, which was discovered in the data. Data analysis revealed that the rate of corporate governance disclosure influences the stock prices of firms, even though profitability, leverage, firm size, and industry did not have any moderating effect on this relationship. These findings show that corporate governance disclosure is a very relevant factor in the decision making of investors in consumer goods firms, which makes it essential for these firms to build trust and display transparency by always disclosing their corporate governance practices in their annual reports, their websites, and other channels.